Single-Sampling Strategy vs. Multi-Sampling Strategy for Blood Cultures in Sepsis: A Prospective Non-inferiority Study - Yu, David; Larsson, Anna; Parke, Åsa; Unge, Christian; Henning, Claes; Sundén-Cullberg, Jonas; Somell, Anna; Strålin, Kristoffer; Özenci, Volkan (Frontiers in Microbiology, 2020)
Background: Optimal sampling is critical for the performance of blood cultures (BC). Most guidelines recommend collecting 40 ml of blood, divided between two venipuncture sites, i.e. multi-sampling strategy (MSS). Sampling through a single venipuncture site, i.e. single-sampling strategy (SSS) is easier, however, the diagnostic performance of SSS compared to MSS remains unknown. Thus, we aimed to study if SSS is non-inferior to MSS for detection of pathogenic microorganisms. Method: A prospective, paired, non-inferiority design was used. Patients with clinically suspected sepsis admitted to an Emergency Department were included. Six BC bottles were simultaneously collected, consisting of four BC bottles from the first arm and two from the other arm. SSS consisted of BC bottles 1, 2, 3, and 4, and MSS consisted of BC bottles 1, 2, 5, and 6. Samples were incubated in a BacT/ALERT blood culture system. Results: The final analysis included 549 episodes. Pathogenic microorganisms were detected in 162 cases (29.5%) with MSS and 160 cases (29.1%) with SSS, yielding an absolute difference of 0.36%, with a 95% confidence interval of -1.33% – 2.06%, which did not exceed the pre-defined non-inferiority margin of 5%. MSS tended to produce more contaminant growth (7.3% of cases) than SSS (5.3% of cases; p = 0.072). Conclusion: The study showed that SSS was non-inferior to MSS in detecting pathogenic microorganisms and supports use of SSS as a routine method.